The hydrogeochemistry of subsurface brines in and west of the Jordan–Dead Sea Transform fault. Issue 3 (19th February 2014) - Möller, P.; Rosenthal, E.; Flexer, A.
Abstract This study is based on 113 analyses of brines with Cl > 0.57 mol l−1 (modern seawater), which were collected and analysed mostly during several decades of exploration for gas and oil in Israel. Based on critical evaluation of correlations of elements and ionic ratios and on spider patterns, six different brine events or source brines were identified in the Phanerozoic: the Triassic, Lower Cretaceous and the Mio/Pliocene brine families which were identified in boreholes Sdom‐1, Sdom Deep‐1 and Ha'on, and the Holocene Dead Sea brines. The Triassic brines are nowadays also encountered in under‐ and overlying rock units such as the Paleozoic Negev‐Yam Suf and the Jurassic Arad Groups, respectively. The southern Jordan–Dead Sea Transform (also known as the Rift) hosts the Mio‐Pliocene Sdom Deep and Sdom brine families. Brine bodies not sufficiently isolated by impervious sedimentary layers were flushed out during the Pliocene when the southern Valley drained north‐ and westwards through the Yizre'el Valley to the Mediterranean Sea. In the northern Rift Miocene to Pliocene seawater evaporated and infiltrated into the Rift sediments and into adjacent rocks. Further diluted by freshwater, it emerges as the Ha'on brine. Together with its derivatives, they form the Ha'on family. The derivatives of the Holocene Dead Sea brine family occur along the shoreline of the recent Dead Sea. Apart of all these evaporation brines, brines deriving from dissolution of evaporites locally occur in the area. The time‐bound chemical composition of paleoseawater is considered when discussing the ionic ratios of brines generated during different geological periods. Spider patterns of each brine family are compared and, where necessary, the relationship of brines to distinct families of brines is supported by inverse modelling.